Assistance of Women's Organizations in the Prevention of Maternal and Child Mortality - Nildawati, Nildawati; Alam, Syamsul; Hajar, Ibnu (Yayasan Mestika Nusantara Satu, 2024)
The increase in the Maternal Mortality Rate not only reflects maternal health problems, but also shows the existence of gender inequality and injustice. The low public awareness of pregnant women's health also contributes to the high number of AKI. Therefore, the participation of women's organizations in society is highly expected to be involved, contribute, and responsible for women's issues. The purpose of this community service activity is to provide assistance and training to women's organizations in an effort to prevent maternal and child deaths. This activity was carried out in the city of Makassar, especially in areas that are the center of women's community organization activities and there are pregnant women. The mentoring was carried out for 3 months, starting from June to August 2023, using pre and post test analysis. The results of this service activity show that women's organizations can play a role as a companion for pregnant women, which is assessed through increasing knowledge and attitudes before and after participating in training.